2014
DOI: 10.3390/su6117921
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Large-Scale Wind Power Integration on Small Signal Stability Based on Stability Region Boundary

Abstract: Abstract:Up until now, study results on the impact of large-scale wind power integration on small signal stability have often been in conflict. Sometimes, the conclusions are even completely opposite, making people unable to agree on which is right. The reason behind this phenomenon is that most of these studies are based on a certain grid and typical working conditions, so conclusions are reached by comparing changes in oscillation mode, one by one. This study method lacks a broader perspective, and often ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Where the frequency of oscillation in Hz, and the damping ratio are given by equation ( 11) and (12).…”
Section: Small Signal Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Where the frequency of oscillation in Hz, and the damping ratio are given by equation ( 11) and (12).…”
Section: Small Signal Stabilitymentioning
confidence: 99%
“…Different methods reported for analyzing a power system's small signal stability include probabilistic methods [11], small signals stabilization area boundaries [12], time domain simulations [7], and modal analysis by measurement of its own value [8]. The limited study of the signal stability with the application of wind power was applied to different power systems.…”
Section: Introductionmentioning
confidence: 99%
“…Here, five distributed energy resources and its controlling strategies were investigated for modernized power systems. Liu et al (2014) studied the impact of large-scale wind power integration on small signal stability. Based on wind farm integration coupled with a single-machine infinite-bus system, it was observed that, compared with the synchronous generator, a wind farm greatly reduces the small signal stability region boundary and the small signal stability of the power system.…”
Section: Related Workmentioning
confidence: 99%
“…As per [7], SSS is dependent on the system operating conditions. Also, as per [8], the SSS is affected by system oscillations due to varying wind generations. In [9], simulations have been conducted in time domain with different renewable sources for SSS enhancements and FACTS-based controllers are found to be much efficient in comparison with conventional PSS as reported by many researches [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%